1996
DOI: 10.1021/jo950899g
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Predictions of Substituent Effects on the Thermal Electrocyclic Ring Openings of Cyclobutenones

Abstract: The transition structures for the electrocyclic ring openings of a variety of substituted cyclobutenones were located with ab initio molecular orbital theory. The effects of substituents on the stereochemistries and activation energies of the electrocyclic ring openings are predicted to be similar to those in cyclobutene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…[17,18] In line with the work of others, [19] our analysis gave a DE value for the diradical 13 A and it was 4.1 kcal mol À1 lower than that for the zwitterionic isomer 13 B (see Figure 1a nd the Supporting Information). To test that hypothesis,w e modelled the reaction using DFT calculations [at the UB3LYP/6-311G(d,p) level].…”
Section: Methodssupporting
confidence: 89%
“…[17,18] In line with the work of others, [19] our analysis gave a DE value for the diradical 13 A and it was 4.1 kcal mol À1 lower than that for the zwitterionic isomer 13 B (see Figure 1a nd the Supporting Information). To test that hypothesis,w e modelled the reaction using DFT calculations [at the UB3LYP/6-311G(d,p) level].…”
Section: Methodssupporting
confidence: 89%
“…Due to the loss of aromaticity, the benzocyclobutenone electrocyclic ring opening is much less favorable than the ring opening of cyclobutenones. 29 The ring opening of the rhodium-bound complex 3 is even less favorable (green pathway in Figure 3) in terms of activation free energies due to unfavorable entropic effects. Thus, the electrocyclic ring opening mechanisms are ruled out.…”
Section: Resultsmentioning
confidence: 99%
“…This zwitterion either undergoes direct ring closure to form β-lactam cis-10, or isomerizes by bond rotation to afford zwitterion 11, which undergoes ring closure to β-lactam trans-10 (Scheme 13). As noted in the Scope and Limitations section (Scheme 30), electronic effects on the sense of rotation (torquoselectivity) in the ring opening and closing of cyclobutenones have been considered, 39 and this concept has been extended to the electrocyclization of the zwitterionic intermediates in the Staudinger β-lactam synthesis. Later work has, however, suggested that the theory of torquoselectivity cannot reliably be used to predict the stereochemical course of β-lactam formation.…”
Section: Scheme 12mentioning
confidence: 99%
“…The torquoselectivity in the thermal ring opening of cyclobutenones 24 has been examined by computational means and proposed to occur with preferential outward rotation of electron donating groups (Scheme 30). 39 The torquoselectivity is usually not high, and the cyclobutenone opening and closing is reversible, so a steady-state concentration of the (Z)-vinylketene will also be present and may lead to observed products. O • O…”
Section: Scheme 29mentioning
confidence: 99%